Importance of microstructure modeling for additively manufactured metal post-process simulations - Sunny, Sumair; Gleason, Glenn; Bailey, Karl; Mathews, Ritin; Malik, Arif (International journal of engineering science, 2021)
•Influence of 3D SLM microstructure induced anisotropy on milling and laser peening.•SLM microstructure inhomogeneity reveals expanded temperature/plastic strain fields.•Shear and ductile damage progression rates in milling vary due to SLM inhomogeneity.•Asymmetry in residual stress clearly evident in LSP from SLM-induced inhomogeneity. [Display omitted] This work investigates the significance of microstructure-level modeling by simulating the material response of an inhomogeneous selective laser melted (SLM) Inconel 625 specimen subjected to two different post-process operations, namely micro-milling and laser shock peening (LSP). A physics-based thermal finite element simulation is executed to obtain the SLM thermal history from which a 3-dimensional inhomogeneous microstructure representative volume element (RVE) is generated via the Dynamic Kinetic Monte Carlo predictive model. A Johnson–Cook plasticity definition coupled with Hall–Petch strengthening is used to define unique yield surfaces for individual grains based on their major diameters. Micro-milling and LSP simulations are subsequently executed with and without considering an inhomogeneous microstructure RVE in attempt to elucidate differences in the plastic strain, temperature, induced stress magnitude and distribution, as well as differences that arise during material removal for the micro-milling only. The micro-milling simulations reveal a greater volumetric distribution of plastic strain and temperature for the inhomogeneous case, although the homogeneous case with isotropic assumption reveals greater heat dissipation at the tool-workpiece interface with 27% greater contact pressure and 39% greater frictional shear stress. Examining the ductile and shear damage progression at a specific time increment reveals that the inhomogeneous model has a slightly lower damage propensity in comparison the homogeneous case, despite having identical damage models and boundary conditions. Variation in the SLM process-dependent yield surfaces, for grains at different locations, results in spatial variations of the computed stress triaxiality, which influences the material removal, as well as the stress concentrations developed near the tool-workpiece interface. Thus, a process-structure-property relationship is captured with the microstructure modeling. This work is the first to illuminate the importance of capturing SLM-induced anisotropy, considering the additively manufactured grain structure subject to micro-milling and LSP post-processes.